Endocrine taste cells. Issue 1 (2nd January 2014) - Kokrashvili, Zaza; Yee, Karen K.; Ilegems, Erwin; Iwatsuki, Ken; Li, Yan; Mosinger, Bedrich; Margolskee, Robert F.
<x content-type="archive" xml:space="preserve">Abstract</x> In taste cells, taste receptors, their coupled G proteins and downstream signalling elements mediate the detection and transduction of sweet, bitter and umami compounds. In some intestinal endocrine cells, taste receptors and gustducin contribute to the release of glucagon-like peptide 1 (GLP-1) and other gut hormones in response to glucose and non-energetic sweeteners. Conversely, taste cells have been found to express multiple hormones typically found in intestinal endocrine cells, e.g. GLP-1, glucagon, somatostatin and ghrelin. In the present study, by immunohistochemistry, multiple subsets of taste cells were found to express GLP-1. The release of GLP-1 from 'endocrine taste cells' into the bloodstream was examined. In wild-type mice, even after oesophagectomy and vagotomy, oral stimulation with glucose induced an elevation of GLP-1 levels in the bloodstream within 10 min. Stimulation of taste cell explants from wild-type mice with glucose led to the release of GLP-1 into the medium. Knocking out of the Tas1r3 gene did not eliminate glucose-stimulated GLP-1 release from taste cells in vivo. The present results indicate that a portion of the cephalic-phase rise in circulating GLP-1 levels is mediated by the direct release of GLP-1 from taste cells into the bloodstream.